The Role of Islamic Principles in Shaping Landscape Architecture: Insights from NTB, Sumenep, and Malaysia - Asrun, Arti Manikam (PILAR, 2025)
This study examines the integration of Islamic principles into landscape architecture, emphasizing the spiritual, ecological, and cultural dimensions of design. Using a qualitative descriptive approach, the paper explores theoretical foundations drawn from the Qur’an and classical Islamic landscapes, alongside empirical cases from Indonesia (West Nusa Tenggara and Sumenep) and Malaysia. The findings demonstrate that Islamic values such as tauhid (unity), mizan (balance), khalifah (stewardship), and ihsan (excellence) provide a normative framework for sustainable landscape design. In Indonesia, pesantren gardens, mosque courtyards, and royal landscapes illustrate how Islamic ethics are localized in vernacular ecologies, while in Malaysia, contemporary Islamic gardens in urban centers reflect institutionalized approaches to sustainable design. By combining Islamic environmental ethics with landscape theory, this research argues that Islamic landscapes are not merely historical relics but evolving practices that strengthen cultural identity, ecological resilience, and spiritual meaning in contemporary urbanism.